Characterization of Waste Material Derived Willemite-Based Glass-Ceramics Doped with Erbium. (9th June 2015) - Sarrigani, G. V.; Quah, H. J.; Lim, W. F.; Matori, K. A.; Mohd Razali, N. S.; Kharazmi, A.; Hashim, M.; Bahari, H. R.
Abstract : We reported, for the first time, to the best of our knowledge, the production of erbium doped willemite-based glass-ceramic using waste material. In this work, a willemite-based glass-ceramic was prepared from waste material to obtain excellent crystallinity and then doped with trivalent erbium (Er 3+ ) to yield ([(ZnO)0.5 (SLS)0.5 ]1− x [Er2 O3 ] x ) final composition where x = 3 wt%. The samples were sintered at various temperatures (500–1100°C) to study the effects of sintering temperatures on microstructure and physical properties of the samples. X-ray diffraction (XRD) and Fourier transform infrared (FTIR) were used to determine structural changes and functional groups in the samples, respectively. Field-emission scanning electron microscopy (FE-SEM) equipped with energy dispersive X-ray was used to observe surface morphology and to detect presence of elements in the samples. Findings showed that average grain size of the Er 3+ doped glass-ceramic sample increased as a function of the sintering temperature and the optimum temperature was 900°C.